Relationship between Demographic Factors and Body Mass Index with the Prevention of Hypertension in Adolescents - Ratna Indriawati; Syaifudin Syaifudin (Masters Program in Public Health, Sebelas Maret University, 2020)
Background: Hypertension or increased blood pressure is often referred as the silent killer because it usually does not show significant signs and symptoms. Thus, almost all patients do not realize if they suffer from hypertension. The Basic Health Research (Riskesdas) 2007 reported that the prevalence of hypertension in the population aged over 18 years old in Indonesia was 31.7%. Because of the increasing prevalence of hypertension in adolescence, it is necessary to take precautions. This study aimed to examine the relationship between demographic factors and body mass index with the prevention of hypertension in adolescentsSubjects and Method: This was a cross sectional study conducted at Muhammadiyah 1 Senior high school, Yogyakarta, from May 2017 to February 2018. A sample of 80 students was selected for this study. The dependent variables were prevention behavior. The independent variables were age, sex, body mass index (BMI), and residence. The data were collected by questionnaire and analyzed by Chi square.Results: 48 (60%) students had good hypertension prevention behavior. Female (OR= 3.00; p= 0.030), urban residence (OR= 2.78; p= 0.040), and normal body weight (OR= 4.30; p= 0.001) increased behavior of hypertension prevention, and they were statistically significant. Older age (OR= 1.59; p= 0.220) increased behavior of hypertension prevention, but it was statistically non-significant.Conclusion: Female, urban residence, normal body weight, and older age increase behavior of hypertension prevention.Keywords: hypertension prevention behavior, demographic factorsCorrespondence: Ratna Indriawati. Department of Physiology, Faculty of Medicine and Health Sciences, Universitas Muhammadiyah Yogyakarta, Yogyakarta 55183 Indonesia. Email: r_indriawatiwibowo@yahoo.comJournal of Health Promotion and Behavior (2020), 5(2): 72-78https://doi.org/10.26911/thejhpb.2020.05.02.01